Binary temporal upconversion codes of Mn2+-activated nanoparticles for multilevel anti-counterfeiting - Xiaowang Liu (Nature Portfolio, 2017)
Luminescent materials that are capable of binary temporal coding are desirable for multilevel anti-counterfeiting. Here, the authors engineer nanoparticles that produce binary color codes on different timescales by combining the long-lived luminescence of Mn2+ with the relatively short-lived emission of lanthanides.